(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
The two American thinkers Stanley Cavell and Eugene Gendlin independently from one another open up perspectives on human experience and language, that strive to overcome conventional concepts based on the tradition of scepticism. Both thinkers are linked to Psychotherapy, yet in very different ways. Stanley Cavell detects at the root of scepticism the experience of alienation from a "world object", and also from the meaning of words: words are treated as if they were labelling things. Eugene Gendlin sees process rather than representation as fundamental for the relation of symbol and experience. In his work he shows how words can be conceived in their interaction with our bodily situation.